Literatur Review: Pengaruh Problem-Based Learning (PBL) terhadap Kemampuan Berpikir Kritis Peserta Didik dalam Memahami Isu Perubahan Lingkungan: Penelitian - Sesil Audia Br Sibarani; Servina Indah Yani Br Tarigan; Ruth Cessaminar Gultom; Ivo Elsa Samaria Hutabarat; Angel Maria Yosephine; Widya Arwita; Rizal Mukra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The increasingly complex issue of environmental change requires students to possess critical thinking skills in order to understand and find solutions to the ecological problems occurring around them. Learning activities in schools still tend to focus on rote memorization, which limits students’ ability to think deeply and analytically about environmental phenomena. The Problem-Based Learning (PBL) model emerges as an innovative student-centered approach that presents real-world problems to be solved through critical and collaborative thinking processes. The purpose of this literature review is to analyze the influence of the PBL model on enhancing students’ critical thinking skills in understanding environmental change issues. Based on the review of previous studies, PBL has been proven effective in improving critical thinking ability, conceptual understanding, and awareness of environmental issues. Therefore, the implementation of PBL can serve as a relevant learning strategy to develop active, reflective students with a high level of ecological awareness.